2022
DOI: 10.1037/emo0000756
|View full text |Cite
|
Sign up to set email alerts
|

Racialized emotion recognition accuracy and anger bias of children’s faces.

Abstract: Research suggests that individuals are racially biased when judging the emotions of others (Elfenbein & Ambady, 2002) and particularly regarding attributions about the emotion of anger (Halberstadt, Castro, Chu, Lozada, & Sims, 2018; Hugenberg & Bodenhausen, 2003). Systematic, balanced designs are rare, and are comprised of adults viewing adults. The present study expands the questions of racialized emotion recognition accuracy and anger bias to the world of children. Findings that adults demonstrate either le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 98 publications
3
57
0
Order By: Relevance
“…Implicit biases toward Black children can misconstrue students' actions when met with these perceptions by authority figures (Bottiani et al, 2018). For instance, prospective teachers are more likely to misperceive Black children as more angry than White children (Halberstadt et al, 2020). Additionally, Smolkowski et al (2016) find that more subjective forms of behavior such as defiance allow for implicit bias to be involved in teachers' decisionmaking; which can negatively impact disciplinary outcomes for Black children.…”
Section: Reasons For the Disproportionate Disciplining Of Black Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit biases toward Black children can misconstrue students' actions when met with these perceptions by authority figures (Bottiani et al, 2018). For instance, prospective teachers are more likely to misperceive Black children as more angry than White children (Halberstadt et al, 2020). Additionally, Smolkowski et al (2016) find that more subjective forms of behavior such as defiance allow for implicit bias to be involved in teachers' decisionmaking; which can negatively impact disciplinary outcomes for Black children.…”
Section: Reasons For the Disproportionate Disciplining Of Black Childrenmentioning
confidence: 99%
“…Sources of this behavioral disproportionality vary; however, there are specific explanations in the research literature that have been suggested. An examination of the existing research base indicates that Black children are included in disparate behavior outcomes for three primary reasons which include implicit bias (Gilliam et al, 2016; Halberstadt et al, 2020), differential treatment and support (Owens & McLanahan, 2020), and perceived disruptive behavior (Yang et al, 2018). More specifically, Black children are often perceived as being less “childlike” and are unwillingly held to adult standards of accountability in regard to their own actions (Epstein et al, 2017; Wegmann & Smith, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Early childhood educators expect and look for more challenging behavior from Black children (Ferguson, 2000; "Problem Children" and "Children with Problems" Freidus 7 Gilliam, Maupin, Reyes, Accavitti, & Shic, 2016). Teachers are more likely to incorrectly perceive Black boys as "angry" when compared to Black girls, white boys, and white girls (Halberstadt et al, 2020). They are also more likely to focus on enforcing rules and delivering consequences, rather than facilitating relationships or rewarding positive behavior, with boys than girls (Dobbs, Arnold, & Doctoroff, 2004;Erden & Wolfgang, 2004).…”
Section: Race Gender and The Good Childmentioning
confidence: 99%
“…However, Kegel et al [15] showed differences in the perception of fearful dynamic avatars and dynamic human faces. Gender [23], culture [8] and race [11] have been reported to influence FER.…”
Section: Virtual Agents and Emotionsmentioning
confidence: 99%